Toxic cyanobacteria and drinking water: Impacts, detection, and treatment - He, Xuexiang; Liu, Yen-Ling; Conklin, Amanda; Westrick, Judy; Weavers, Linda K.; Dionysiou, Dionysios D.; Lenhart, John J.; Mouser, Paula J.; Szlag, David; Walker, Harold W. (Harmful algae, 2016)
Blooms of toxic cyanobacteria in water supply systems are a global issue affecting water supplies on every major continent except Antarctica. The occurrence of toxic cyanobacteria in freshwater is increasing in both frequency and distribution. The protection of water supplies has therefore become increasingly more challenging. To reduce the risk from toxic cyanobacterial blooms in drinking water, a multi-barrier approach is needed, consisting of prevention, source control, treatment optimization, and monitoring. In this paper, current research on some of the critical elements of this multi-barrier approach are reviewed and synthesized, with an emphasis on the effectiveness of water treatment technologies for removing cyanobacteria and related toxic compounds. This paper synthesizes and updates a number of previous review articles on various aspects of this multi-barrier approach in order to provide a holistic resource for researchers, water managers and engineers, as well as water treatment plant operators.